Expression of LHCGR in Pheochromocytomas Unveils an Endocrine Mechanism Connecting Pregnancy and Epinephrine Overproduction. Issue 5 (22nd February 2022) - Lopez, Antoine-Guy; Duparc, Céline; Renouf, Sylvie; Machevin, Elise; Le Guillou, Vincent; Sabourin, Jean-Christophe; Defortescu, Guillaume; Buffet, Alexandre; Gimenez-Roqueplo, Anne-Paule; Dubessy, Christophe; Louiset, Estelle; Lefebvre, Hervé
Abstract : Background: The mechanisms by which pregnancy may unmask pheochromocytomas and paragangliomas are not totally understood. We hypothesized that gestational hormones may participate in the pathophysiology of catecholamine excess during pregnancy. We report a case of silent pheochromocytoma revealed in a pregnant woman by life-threatening adrenergic myocarditis. Methods: In vitro studies were conducted to investigate the effect of estradiol and the pregnancy hormone hCG (human chorionic gonadotropin) on epinephrine secretion by cultured cells derived from the patient's tumor. Expression of LHCG (luteinizing hormone/chorionic gonadotropin) receptor was searched for in the patient's tumor, and a series of 12 additional pheochromocytomas by real-time reverse transcription polymerase chain reaction and immunohistochemistry. LHCGR expression was also analyzed in silico in the pheochromocytomas and paragangliomas cohorts of the Cortico et Médullosurrénale: les Tumeurs Endocrines and The Cancer Genome Atlas databases. Results: hCG stimulated epinephrine secretion by cultured cells derived from the patient's pheochromocytoma. The patient's tumor expressed the LHCG receptor, which was colocalized with catecholamine-producing enzymes. A similar expression pattern of the LHCG receptor was also observed in 5 out of our series of pheochromocytomas. Moreover, in silico studies revealed that pheochromocytomas and paragangliomas display the highest expression levels of LHCG receptor mRNA among the 32 solid tumor types of The Cancer Genome Atlas cohort. Conclusions: Pregnancy may thus favor surges in plasma catecholamine and hypertensive crises through hCG-induced stimulation of epinephrine production by pheochromocytomas.